2009
DOI: 10.1152/ajpgi.90703.2008
|View full text |Cite
|
Sign up to set email alerts
|

Vascular stasis, intestinal hemorrhage, and heightened vascular permeability complicate acute portal hypertension in cd39-null mice

Abstract: Sun X, Cá rdenas A, Wu Y, Enjyoji K, Robson SC. Vascular stasis, intestinal hemorrhage, and heightened vascular permeability complicate acute portal hypertension in cd39-null mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…As expected, 7 days after PPVL control mice displayed significant splenomegaly with an increased spleen-to-body (g/g) weight ratio (0.51 Ϯ 0.069) ( Fig. 2C), which is consistent with the published data (22,52). Interestingly, however, EGKO mice developed more pro- nounced splenomegaly (Fig.…”
Section: Endothelial Gab1 Expression Is Increased By Ph In a Timedepesupporting
confidence: 91%
“…As expected, 7 days after PPVL control mice displayed significant splenomegaly with an increased spleen-to-body (g/g) weight ratio (0.51 Ϯ 0.069) ( Fig. 2C), which is consistent with the published data (22,52). Interestingly, however, EGKO mice developed more pro- nounced splenomegaly (Fig.…”
Section: Endothelial Gab1 Expression Is Increased By Ph In a Timedepesupporting
confidence: 91%
“…There are multiple examples showing that application of inhibitors such as the nucleotide analogue ARL 67156 potentiate nucleotide-mediated neurotransmission [170][171][172][173]. Deletion of NTPDase1 in mice revealed a key role of this enzyme in the prevention of thrombosis [41,42], in purine signaling in angiogenesis [174], vascular permeability [175,176], vascular relaxation [49], in the control of macrophage function [177], or also in promoting tumor growth [178]. Accordingly, transgenic mice expressing human NTPDase1 exhibited impaired platelet aggregation and were protected from thrombosis in a transplantation setting [179].…”
Section: Downstream Signaling Nucleotidesmentioning
confidence: 99%
“…Using pharmacological and genetic approaches, a number of studies have demonstrated that extracellular ATP signaling, mainly through P2X1 receptor activation, modulates adrenergic-mediated control of vascular tone in both rat hepatic artery and portal vein systems (4749). Also, it has been recently shown that ATP stimulation increases portal vein pressure in Cd39 −/− mice upon administration of nitric oxide (NO) inhibitor L-NG-Nitroarginine, suggesting a P2X-dependent vasoconstrictive effect, in absence of P2Y-mediated NO release (50). …”
Section: Modulation Of Liver Functions By P2x Receptorsmentioning
confidence: 99%